AGRICULTURAL INSURANCE UNDER THE SOLVENCY II DIRECTIVE - Njegomir, Vladimir; Tepavac, Rajko; Obradović, Miloje (Economics of Agriculture, 2014)
Solvency II Directive represents a new framework of unique solvency regulation of insurance and reinsurance companies in the European Union. Although it has not yet been implemented in national legislations, it can be concluded, based on the directive wording and conducted quantitative studies, that it will have implications on agricultural producers since they are the users of insurance services. The aim of the research presented in this paper is to analyse the implications of the new directive to agricultural producers since they are the insureds and the main actors of agribusiness. Firstly, the paper gives an overview of the basic features of the new regulatory framework and then it points at the issues and the needs for intensive application of Directive in order to improve the insurance business in Serbia. The process will direct the settlement of major claims, the ones that are typical of catastrophic risks in agriculture, towards the insurance, while the expectations from the government will be directed towards the regulation of the setting and economic measures (development and investment subsidies, cooperative movement). In addition, the paper points at the demands of the new regulation and analyses the implications of the new regulation regarding the settlement of claims resulting from major flood since it represents the example that proves the basic postulate.